Association of Advanced Glycation End Products With Lower-Extremity Atherosclerotic Disease in Type 2 Diabetes Mellitus - Ying, Lingwen; Shen, Yun; Zhang, Yang; Wang, Yikun; Liu, Yong; Yin, Jun; Wang, Yufei; Yin, Jingrong; Zhu, Wei; Bao, Yuqian; Zhou, Jian (Frontiers in Cardiovascular Medicine, 2021)
Aims: Advanced glycation end products (AGEs) were reported to be correlated with the development of diabetes, as well as diabetic vascular complications. Therefore, this study aimed at investigating the association between AGEs and lower extremity atherosclerotic disease (LEAD). Methods: A total of 1,013 type 2 diabetes patients were enrolled. LEAD was measured through color Doppler ultrasonography. The non-invasive skin autofluorescence method was performed for AGEs measurement. Considered that age plays an important role in both AGEs and LEAD, age-combined AGEs, i.e., AGEage index (define as AGE × age / 100) was used for related analysis. Results: The overall prevalence of LEAD was 48.9% (495/1013). Patients with LEAD showed a significantly higher AGEage (P < 0.01), and the prevalence of LEAD increased with ascending AGEage levels (P for trend < 0.001). Logistic regression analysis revealed that AGEage was significantly positively associated with risk of LEAD, and the odds ratios of presence of LEAD across quartiles of AGEage were 1.00, 2.18 [95% confidence interval (CI) 1.42–3.35], 3.68 (95%CI 2.37–5.73) and 5.44 (95%CI 3.39–8.71) for multivariable-adjusted model (both P for trend < 0.001), respectively. The results were similar among patients of different sexes, body mass index (BMI) and with or without diabetes family history. Further, AGEage presented a better predictive value for LEAD than glycated hemoglobin A1c (HbA1c), with its sensitivity, specificity and area under the curve (AUC) of 75.5% (95%CI 71.6–79.2%), 59.3% (95%CI 54.9–63.6%) and 0.731 (0.703–0.758), respectively. Conclusion: AGEage, the non-invasive measured skin AGEs combined with age, seems to be a more promising approach than HbA1c in identifying patient at high risk of LEAD.